A liposomal curcumol nanocomposite for magnetic resonance imaging and endoplasmic reticulum stress-mediated chemotherapy of human primary ovarian cancer. Issue 18 (24th April 2019) - Wang, Jing; Song, Yonghong; Zhang, Mingxun; Wu, Zhensheng; Xu, Yun-Jun; Lin, Jun; Ling, Daishun; Sheng, Youjing; Lu, Yang; Wu, Qiang
Abstract : A liposomal curcumol nanocomposite has been successfully synthesized for the theranostics of human primary ovarian cancer cells from solid tumor tissue in patients. Abstract : Combination chemotherapy has improved the life quality of patients suffering from ovarian cancer; however, drug resistance and late relapse lead to a high mortality rate. As a bioactive component in zedoary oil, curcumol has been widely used against gynecological tumors in the clinic. However, the bioavailability of curcumol is limited by its indissolubility in water. The design of nano-formulas is promising to improve traditional drugs in the clinic, which is beneficial for the treatment of malignant diseases, especially cancer. Herein, a liposomal curcumol nanocomposite was prepared for the theranostics of human primary ovarian cancer cells from solid tumor tissue in patients. In this uniform nanocomposite, curcumol and a frequently used magnetic resonance contrast agent, gadopentetate dimeglumine (Gd-DTPA), were effectively wrapped in the hydrophobic lipid bilayer and aqueous cavity of the liposome, respectively. Parallel assessments of the anti-tumor ability and mechanism of liposomal curcumol were performed on both SKOV3 and human primary ovarian cancer cells, and the results indicated the induction of apoptosis in ovarian cancer cells by this curcumol nanocomposite via the endoplasmic reticulum pathway. Liposomal curcumol has been further confirmed to inhibit the growth of SKOV3 human ovarian cancer xenografts on tumor-bearing nude mice. Moreover, this gadolinium-based liposomal curcumol nanocomposite exhibited excellent T 1 -weighted magnetic resonance imaging (MRI) capability for the efficient detection of xenograft ovarian cancer, leading to a novel multifunctional therapeutic agent.